Analisis Pengaruh Tingkat Partisipasi Angkatan Kerja dan Upah Minimum Provinsi Terhadap Kemiskinan Di Provinsi Banten - Desmawan, Deris; Salsabila, Adinda Kanza; Amalia, Lia; Anargya, Raffy Amantha; Kirana, Rahma Sasi; Valentina, Valentina (Jurnal Manajemen Akuntansi (JUMSI), 2023)
The influence of labor force participation rates and minimum wages on poverty in Banten province is an issue of concern to many parties. According to data from the Central Statistics Agency (BPS), in 2019 the poverty rate in Banten Province reached 8.19%, or around 1.5 million residents. This figure is higher than the national average of 9.22%. One factor that is considered very influential in overcoming poverty is the availability of employment. Productive and quality Labor Force Participation Rate (TPAK) can increase people's income and reduce poverty. The purpose of this study was to see the effect of the Labor Force Participation Rate and Banten Provincial Minimum Wage on Poverty. Panel data analysis was performed to prove the hypothesis using the ordinary least square method. The results showed that the Provincial Minimum Wage variable had a negative and insignificant effect on the number of poor people, while the labor force participation rate had a significant and positive effect on poverty in Banten Province.